Irregular plurals: an ingenious way of teaching grammar - Elisabete Silva; Cláudia Martins (Instituto Politécnico de Bragança, 2016)
The main purpose of our paper is to focus on the intrinsic nature of irregular plurals in order to understand the evolution of English throughout the centuries. We intend to show how teaching and learning the irregular plurals can be not only of the utmost importance, but also good fun. By presenting creative activities, we wish to make teachers aware of these issues in the teaching of English as a foreign language. Keywords: English as a Foreign Language; irregular plurals; Old English; Middle English; Modern English.